2018
DOI: 10.5606/ehc.2018.59268
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different fixation methods of bicolumnar acetabular fractures

Abstract: In double column fractures, if the reduction does not require an anterior approach, it is not necessary to fix the iliac wing fracture only to improve the stability of the fixation. If the reduction does require an anterior approach, it is worth fixing the iliac wing fracture with the technically less demanding screw fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The current biomechanical finite element study of acetabular internal fixation has two limitations: (1) inaccurate description of fracture morphology, and (2) not already defined width and thickness of the plate as well as diameter & length of screws, resulting in low comparability of experiment. 18 , 23 , 24 Biomechanical studies have shown that the stress on the weight-bearing area of acetabular dome is the most concentrated, which requires anatomical reduction and effective fixation. 21 , 22 If the implant cannot effectively fix the displaced articular fragments, postoperative movements will result in reduction loss, implant loosening or rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The current biomechanical finite element study of acetabular internal fixation has two limitations: (1) inaccurate description of fracture morphology, and (2) not already defined width and thickness of the plate as well as diameter & length of screws, resulting in low comparability of experiment. 18 , 23 , 24 Biomechanical studies have shown that the stress on the weight-bearing area of acetabular dome is the most concentrated, which requires anatomical reduction and effective fixation. 21 , 22 If the implant cannot effectively fix the displaced articular fragments, postoperative movements will result in reduction loss, implant loosening or rupture.…”
Section: Discussionmentioning
confidence: 99%
“…2. The width and thickness of the plate, the diameter and length of screw are not defined, resulting in low repeatability of experiment [18,[23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This might be a considerable factor influencing fracture healing, although we proved in our previous experiments that after fixation of the anterior column (our system is suitable also for this thanks to the grooves), the iliac bone did not require any additional fixation. [6] As a supplement, we provided CT scans taken under load three months after surgery. According to the results of simulation, the screw exposed to the strongest stress broke.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to our former calculations and measurements, the system may be properly simplified: the cancellous bone mass with lower stress resistance cannot be considered negligible, compared to the predominant cortical bone substance; however, it may be averaged, and the ligament system not providing any physical stress transmission due to the injury can be neglected. [6] Accordingly, solid-state physics constants applied in our measurements are represented (Table I).…”
Section: Methodsmentioning
confidence: 99%